Analysis of Contact Mechanical Characteristics of Flexible Parts in Harmonic Gear Reducer - Fanjie Li; Xiaopeng Li; Yajing Guo; Dongyang Shang (Shock and Vibration)
Harmonic gear reducer is widely used in industrial robots, aerospace, optics, and other high-end fields. The failure of harmonic gear reducer is mainly caused by the damage of flexible bearing and flexspline of thin-walled vulnerable components. To study the contact mechanical characteristics of flexible components such as flexible bearing and flexspline in harmonic gear reducer, the contact mechanical model of flexible bearing, vibration differential equation of flexspline, and finite element model of each component in harmonic gear reducer were established. Based on the established model of harmonic gear reducer, the influence of the length of flexspline cylinder and the thickness of cylinder bottom on the stress of flexspline is discussed, respectively, and the motion characteristics of flexible bearing are studied. At the same time, the spatial distribution of the displacement of the flexspline and the axial vibration response of the flexspline are studied. The correctness of the model established in this paper is verified by experiments. The results show that the increase of cylinder length can improve the stress of flexspline in harmonic gear reducer; the wall thickness of cylinder bottom mainly affects the stress at the bottom of flexspline but has little effect on the stress of gear ring and smooth cylinder. Along the axis direction of the flexspline, the radial displacement, circumferential displacement, and angular displacement increase linearly with the increase of the axial distance between the cylinder and the bottom. When the excitation frequency is high, the vibration mode of flexspline shell is mainly axial vibration. The research results will provide a theoretical reference for the optimal design of harmonic gear reducer and improving the service life of flexible parts.